Pengaruh Dewan Komisaris dan Direksi terhadap Kinerja Perusahaan - Audrey Fryda Roselind; Dyah Ratnawati (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine whether there is an influence of the board of commissioners and directors on the company's performance in State-Owned Enterprises listed on the Indonesia Stock Exchange in 2017-2020. The type of research is quantitative, and the data collection technique is the documentation method. Data analysis was performed using multiple linear regression, descriptive analysis and classical assumption tests such as autocorrelation, heteroscedasticity, multicollinearity, R2 test, F test and t test. In addition, this research also uses the help of the SPSS application. The results of the study indicate that there is a significant effect of the board of commissioners on the company's performance and partially, there is no influence of the board of directors on the company's performance. The conclusion is that the board of commissioners has an effect on the company's performance while the board of directors has no influence on the company's performance.